2021
DOI: 10.3390/v13071266
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus as an Uninvited Guest in the Response to Vaccines in People Living with HIV

Abstract: In stark contrast to the rapid development of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), an effective human immunodeficiency virus (HIV) vaccine is still lacking. Furthermore, despite virologic suppression and CD4 T-cell count normalization with antiretroviral therapy (ART), people living with HIV (PLWH) still exhibit increased morbidity and mortality compared to the general population. Such differences in health outcomes are related to higher risk behaviors, but also to HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…The results presented also highlight the relevance of considering the heterogeneity of CMV seropositivity and aging in the design of clinical trials or new vaccines in some clinical conditions such in HIV patients. Thus, CMV-induced chronic immune activation and premature immunosenescence in people living with HIV must be taken into consideration not only when comparing trial outcomes between various populations exhibiting diverse CMV positivity rates but also for HIV vaccine development [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results presented also highlight the relevance of considering the heterogeneity of CMV seropositivity and aging in the design of clinical trials or new vaccines in some clinical conditions such in HIV patients. Thus, CMV-induced chronic immune activation and premature immunosenescence in people living with HIV must be taken into consideration not only when comparing trial outcomes between various populations exhibiting diverse CMV positivity rates but also for HIV vaccine development [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“… 35 Nevertheless, CMV infection, through induction of inflammation, is believed to participate in immune aging, including decreased response to vaccine. 36 , 37 …”
Section: Latent By Not Silent CMV Coinfection In Plwh Receiving Artmentioning
confidence: 99%
“… 42 , 43 By skewing the immune system and persistently stimulating immune cells, CMV contributes to the inflammaging and notably a decreased response to vaccines. 36 …”
Section: Latent By Not Silent CMV Coinfection In Plwh Receiving Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if this interaction is still elusive and additional large scale studies are recommended (16), CMV testing and treatment should be taken into consideration in such critical conditions (18). CMV status must be taken into account for several vaccine responses, especially cancer despite the use of HCMV-based therapeutic cancer vaccines (20), since it has been suggested that with advanced age and due to CMV-associated altered immunity in both healthy and immunocompromised hosts, vaccine immunogenicity was modulated (21)(22)(23). Thus, recent studies are concerned about targeting HCMV to decrease the sensitivity to other infectious diseases and cancer, and to prevent poor responses to vaccination (21,22).…”
Section: Introductionmentioning
confidence: 99%